I totally funniest / 3. - Patterson, James, 1947- (I Funny, 2015)
As the Planet's Funniest Kid Comic finals near, Jamie faces a whirlwind of attention at school and in the media and the fame starts to go to his head, but in Hollywood with Uncle Frankie, some of his fellow comedians quickly show him what competition and pressure are all about.